TAFSIR ALQURâ€™AN PARADIGMA INTEGRATIF: STUDI ATAS QIRAâ€™AH ALTHANIYAH MUHAMMAD SYAHRUR - Abdul Malik (UIN Raden Mas Said Surakarta, 2017)
This article describes on the alternative reading (qira'ah altaniyah) of Alqurâ€™an proposed by Muhammad Shahrur, in his work â€œAlkitab wa Alqurâ€™an: Qira'ah Almu'ashirahâ€. Through this work, Syahrur proposed an integrative-interpretation method which is built through combining analysis of natural science, social science, and tafsir. Based on the descriptive analysis approach to this works, this study found out two important things: (1) Syahrur using mathematical analysis to interpret the muhkamatâ€™s verses and science analysis for mutasyabihatâ€™s verses. (2) Hudud is a result of the integrative analysis interpretation based on the linguistic and mathematic analysis in understanding the Quranic verses about the law, while taâ€™wil ilmi is an understanding toward mutasyabihat verses, like the revelation, which is based on the analysis of natural science cognitive.Â